Impact Of Investment Types And Firm Characteristics On Capital Budgeting Techniques - RAJAH, HEMAWATHY JESSICA (2005)
Capital budgeting decision is a crucial decision for firms. Various capital budgeting techniques are available to help firms in proper analysis of investment projects. Each technique has its own strengths and limitations.